Lepanthes chalalensis (Pleurothallidinae), a new species endemic to the Santander department in Colombia - Parra-Sánchez, Edicson; Restrepo, Eugenio; Barrera, Yadir; Ordóñez-Blanco, Juan Camilo; Edwards, David (Lankesteriana: International Journal on Orchidology, 2024)
We propose Lepanthes chalalensis as a newly identified species confined to the north-east Andes of Colombia. We randomly placed 341 sampling plots across the Eastern Cordillera, including transformed and natural habitats. Here, we provide a detailed description, illustrating images, ecological discussions, a taxonomic key for the new entity, and a conservation status analysis. The species is highly geographically restricted (in 2 out of 341 sampling plots) and has a low population size (26 adult individuals). While L. chalalensis shows a resemblance to L. velosa from Ecuador, it can be distinguished by the wide lower lobe of the petals, which is long ciliated, the lip laminae, which are reduced and bear stiff cilia, and the appendix length, which appear to be twice as long as the lip blades. The species should be considered a conservation concern due to its high rarity.